Mirror Mechanism Behind Visual–Auditory Interaction: Evidence From Event-Related Potentials in Children With Cochlear Implants - Wang, Junbo; Liu, Jiahao; Lai, Kaiyin; Zhang, Qi; Zheng, Yiqing; Wang, Suiping; Liang, Maojin (Frontiers in Neuroscience, 2021)
Abstract: The mechanism behind visual induced auditory interaction is still under discussion. Here we provide some evidence that mirror mechanism can be one of the reasons behind visual-auditory interaction. In this study, visual stimulus was divided into two major groups: 1. Mirror stimulus which was able to activate mirror neurons; 2. Non-mirror stimulus which was not able to activate them on the contrary. The two groups were further divided into six subgroups: 1.1. Visual speech related mirror stimulus; 1.2. Visual speech irrelevant mirror stimulus; 2.1 to 2.4. Non-mirror stimulus with four different level of luminance. Through event-related-potential (ERP) and speech recognition test in cochlear implant children, there were some major results: 1. P1, N1 and P2 ERP components between mirror stimulus and non-mirror stimulus showed significant difference; 2. ERP component difference between mirror stimulus and non-mirror was partly driven from Brodmann area 41 and Brodmann area 42 in Superior Temporal Gyrus; 3. ERP component difference between visual speech related mirror stimulus and non-mirror was partly driven from Brodmann area 39 (visual speech area), which could not be observed in comparison of visual speech irrelevant stimulus group and non- mirror group; 4. ERP evoked by speech related mirror stimulus group had more components correlated with speech recognition than ERP evoked by most non-mirror stimulus, while ERP evoked by speech irrelevant mirror stimulus group could not reach the significant difference with non-mirror stimulus group. Results implied that: 1. Mirror stimulus was different from non-mirror stimulus in neural activation. 2. Visual-auditory interaction possibly lead to ERP difference, as BA (Brodmann area) 41 and 42 make up primary auditory cortex. 3. Mirror neurons was possibly related to ERP difference, considering the function of Brodmann area 39 is correspond to the executing process of information in speech related mirror stimulus. 4. Speech related mirror stimulus could better reflect speech recognition ability. Those were consistent with the hypothesis deduced by mirror mechanism being a mechanism behind visual-auditory interaction.